Hide beetle Dermestes maculatus DeGeer - Brianna Shaver; Phillip Kaufman (EDIS)
EENY466, a 5-page illustrated fact sheet by Brianna Shaver and Phillip Kaufman, is part of the Featured Creatures collection. It describes this beetle that feeds on carrion and dry animal products and has forensic significance in helping to estimate the postmortem interval in suicide or homicide cases — synonymy, distribution, description, life cycle and biology, forensic importance, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, November 2009.